A Guide to Left Bundle Branch Area Pacing Using Stylet-Driven Pacing Leads - De Pooter, Jan; Wauters, Aurelien; Van Heuverswyn, Frederic; Le polain de Waroux, Jean-Benoit (Frontiers in Cardiovascular Medicine, 2022)
Left bundle branch area pacing (LBBAP) has emerged as a novel pacing modality which aims to capture the left bundle branch area and avoids the detrimental effects of right ventricular pacing. Current approaches for LBBAP have been developed using lumen-less pacing leads (LLL). Expanding the tools and leads for LBBAP might contribute to a wider adoption of this technique. Standard stylet-driven pacing leads (SDL) differ from current LLL as they are characterized by a wider lead body diameter, are stylet-supported and often have a non-isodiametric extendable helix design. Although LBBAP can be performed safely with SDL, the implant technique of LBBAP differs compared to LLL. In the current overview we describe in detail how different types of SDL can be used to target a deep septal position and provide a practical guide on how to achieve LBBAP using SDL.